Influence of NOS1AP Risk Variants on the Corrected QT (QTc) Interval in the Pharmacotherapy of Schizophrenia - Esen, Dilhan; Kopf, Juliane; Hägele, Sandra; Plichta, Michael M.; Reif, Andreas; Freudenberg, Florian (Pharmacopsychiatry, 2022)
Introduction The variants of the gene for nitric oxide synthase 1 adaptor protein (NOS1AP) are associated with schizophrenia and cardiovascular deficits involving corrected QT (QTc) interval prolongation. Here, we investigated a possible pharmacogenetic effect of antipsychotic treatment on QTc length in interaction with two NOS1AP variants (rs12143842 and rs10494366) whose minor alleles are associated with increased QTc interval length.Methods We conducted a retrospective analysis of electrocardiographic (ECG) and genotype data of 239 patients diagnosed with schizophrenia. We converted antipsychotics dosage to chlorpromazine equivalents and defined daily doses. We analysed the effects of the minor (i. e. rs12143842-CT/TT and rs10494366-GT/GG) and major (i. e. rs12143842-CC and rs10494366-TT) allele genotypes to QTc interval for female and male participants separately.Results As expected, rs12143842 and rs10494366 exhibit strong linkage disequilibrium. Both polymorphisms had no direct effect on antipsychotic use or QTc interval. However, there was a continuous increase in QTc interval with increasing antipsychotic dosage in males. For both variants, positive correlation of QTc length with antipsychotic dosage was found in homozygous male carriers of the major alleles (i. e. rs12143842-CC and rs10494366-TT), but not in minor allele carriers. There was no significant interaction between antipsychotic dosage and QTc interval for either genotype in female patients.Conclusions In this study, a significant interaction was found between both NOS1AP variants, rs12143842 and rs10494366, and antipsychotic treatment on the QTc interval in a sex-dependent manner. Our findings might be relevant for adequate antipsychotic treatment in rs12143842 and rs10494366 major allele carriers.
Keywords: NOS1AP; CAPON; QTc interval; antipsychotic treatment; pharmacogenetic interaction